The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1002/bit.260300206
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a wild strain of Schizophyllum commune: Cellulase and xylanase production and formation of the extracellular polysaccharide Schizophyllan

Abstract: A wild strain of schizophyllum commune (Fr:Fr:) isolated in Bangladesh produced cellulase and xyianase in high yields as well as the exobiopolymer schizophyllan. It was found experimentally that concentrations of 4% Avicel, 3.5% peptone, and 0.5% Ca(NO(3))(2).4H(2)O were optimal for growth and product formation. Bacto-peptone was found to be the most suitable substrate of a number of casein, mycological, and meat peptone preparations for enzyme production. Young plate-culture inocula (4 days) were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 23 publications
0
28
1
1
Order By: Relevance
“…The experimentally measured enzyme activity (43.51 U/mL) matches the predicted value and represents a 7.2-fold enhancement to BGL activity. Additionally, this optimized medium induced a significant amount of BGL production, contrary to previous reports of BGL production with other S. commune strains: Desrochers et al (1981) and Steiner et al (1987) reported maximum BGL activity of 22.2 U/ml and 34.9 U/ml, respectively, under optimized conditions at 30 °C. …”
Section: Optimization Of Culture Medium Components By Applying Rsmcontrasting
confidence: 94%
“…The experimentally measured enzyme activity (43.51 U/mL) matches the predicted value and represents a 7.2-fold enhancement to BGL activity. Additionally, this optimized medium induced a significant amount of BGL production, contrary to previous reports of BGL production with other S. commune strains: Desrochers et al (1981) and Steiner et al (1987) reported maximum BGL activity of 22.2 U/ml and 34.9 U/ml, respectively, under optimized conditions at 30 °C. …”
Section: Optimization Of Culture Medium Components By Applying Rsmcontrasting
confidence: 94%
“…At 55 ° C fl-glucosidase was most rapidly inactivated followed by FPase and xylanase, losing about 78%, 72% and 59% activity respectively in 72 h. At 50°C the FPase of this strain showed stability similar to that of T. reesei (Reese and Mandels 1980), but at 55°C it was less stable than G. virens FPase (Gomes et al 1989a). At all temperatures tested the fl-glucosidase and xylanase of this strain showed better stability than those of G. virens (Gomes et al 1989a), Schizophyllum c o m m u n e (Steiner et al 1987a) and T. reesei or T. viride (Coughlan 1985). The long-term pH stability of FPase, xylanase and fl-glucosidase is shown in Fig.…”
Section: Bioprocess Experimentsmentioning
confidence: 91%
“…To enhance cellulase production by microorganisms and reduce production costs several efforts such as mutation (Gallo et al 1978), gene cloning (Shoemaker et al 1983), protoplast fusion (Ogawa et al 1987) and optimization of medium composition and environmental factors (Enari and Markkanen 1977;Mandels and Andreotii 1978;Ryu and Mandels 1980;Desrochers et al 1980;Steiner et al 1987a;Gomes et al 1989a) have been made. Moreover, enzyme production has been increased markedly by the mode of fermentation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are the most potent xylanase producers, as they secrete high level of enzymes than those of yeast and bacteria (Qinnghe et al 2004). Fungus Thielaviopsis basicola which cause black rot in roots of several plants (Baruah et al 1980) is the selective producer of xylanases and cellulases from an industrial point of view due to the extracellular release of xylanases in fermentation broth with an appreciable yield as compared to yeast and bacteria (Haltrich et al 1996;Steiner et al 1987). Production of enzymes like other microbial derived metabolites is generally influenced by several physical and physico-chemical parameters such as incubation temperature, pH of medium, inorganic metals, agitation, aeration and others (Sreenivas Rao et al 2008).…”
Section: Introductionmentioning
confidence: 99%